Designing a unity PF converter for AC drive application - Muhammad Hakim Bin Jamaludin (Nanyang Technological University, 2023)
Sustaining the Power Factor(PF) of a power system is a very important aspect to deliver and obtain high efficient working power. PF is the ratio of True Power(kW) to Apparent Power(kVA) and it measures the efficiency of power conversions. However, research and studies has shown that the PF is not only dependent on the source inductance as it can be controlled by implementing a method known as “Power Factor Correction” (PFC), this methodology is by balancing both capacitive and inductive loads. Apart from PFC methodology, PFs can also be regulated by pulse switching method using numbers of bi-directional low power static switches. Harmonic signals also reduces power systems PF. For example in a three phase Rectifier-Inverter(RI) circuit, PF is non-unity due to Total Harmonic Distortions(THD) which affects current sinusoidal wave form to be distorted and consequently lowers the PF ratio. In addition, harmonics generated by non-linear load reduces system efficiency, apparatus overheating and ineffective costings. Fortunately, there are Harmonic Filters to shunt out these distortions and this could be implemented into the RI circuit for PF improvements.